4.8k views
4 votes
P+h= 43
4.5p+12h=276

1 Answer

2 votes

9514 1404 393

Answer:

(p, h) = (32, 11)

Explanation:

We can write an expression for p using the first equation, then substitute that into the second equation.

4.5(43-h) +12h = 276 . . . . substitute for p

193.5 +7.5h = 276 . . . . . . eliminate parentheses

7.5h = 82.5 . . . . . . . . . . . . subtract 193.5

h = 82.5/7.5 = 11 . . . . . . . . divide by the coefficient of h

p = 43 -11 = 32

The solution is (p, h) = (32, 11).

User Gricel
by
4.5k points